A CLINICAL CASE OF EARLY PRENATAL DIAGNOSIS OF DIASTEMATOMYELIA - Elgina, Svetlana Ivanovna; Abramova, Lyudmila Viktorovna; Stopicheva, Svetlana Leonidovna; Kokina, Elena Aleksandrovna; Solovieva, Olga Arkadyevna; Geld, Yulia Germanovna; Sergeeva, Anna Vladimirovna; Rudaeva, Elena Vladimirovna; Moses, Kira Borisovna; Moses, Vadim Gelievich (Mother and Baby in Kuzbass, 2026)
Closed spinal dysraphia (spina bifida occulta) is a form of congenital spinal bifida in which the bony defect is hidden under intact skin. The population frequency of closed spinal dysraphia has not been definitively determined. According to the data of modern studies, the frequency of detection of spinal dysraphia is 0.5-2.5%. Nevertheless, due to its relative rarity, diagnostic challenges, and limited literature coverage, diastematomyelia remains an underrecognized condition for many healthcare professionals, emphasizing the need for further research and dissemination of knowledge.The article describes an early case of prenatal ultrasound diagnosis of diastematomyelia at 13.4 weeks of pregnancy.
Keywords: fetus; spinal dysgraphia; diastematomyelia; prenatal diagnosis